An Investigation of a Frontal Negative Slow Wave in a Virtual Hedonic Purchase Task - Mei, Yupeng; Jing, Kunpeng; Chen, Lele; Shi, Rui; Song, Zhijie (Frontiers in Human Neuroscience, 2021)
There is a connection between the Frontal Negative Slow Wave (FNSW) and the arousal inhibition in the hedonic purchase context. To calculate the FNSW (400-800 ms), event-related potentials (ERPs) method was applied to depict the neural substrates on prudent and impulsive consumers’ behaviors within various states of promotion. Promotion types include the pure price promotion and the mixed promotion (a mixture of a charitable donation and a discount). Behaviorally, consumers response more quickly in the pure price promotion condition and they express a preference for the mixed promotion. More importantly, a larger FNSW emerged in the impulsive consumers than the prudent, suggesting that the former might tend to control their eagerness to consume hedonic items. Compared with the price promotion as the worse option, the mixed promotion as the better option caused more perceptual conflict, leading to an increase in N2 amplitude. It suggests that consumers incline to reject the worse offers. These results also reveal that people primarily have to search negative promotion information by their insight and subsequently impulsive consumers inhibit the responses to the promotion information. The method of ERPs and FNSW should be helpful for marketing researchers and professionals on hedonic consumption and sales promotion.